The Genomic Tools for Sweetpotato Improvement (GT4SP) Project - International Potato Center (2017)
The GT4SP project, launched in September 2014, is a four-year investment to develop genomic and genetic resources for sweetpotato improvement with the goal of establishing molecular marker-assisted breeding resources for the global sweetpotato breeding community. We have several “firsts” already in generating new genetic resources.